Pengaruh Salinitas Air Laut Terhadap Laju Korosi Pada Plat Lambung Kapal Bobot 1500 DWT - Lilik Budiyanto (Politeknik Ilmu Pelayaran Semarang, 2021)
Ships are a means of transportation over the sea, where ships play a vital role in the socio-economic aspect through their distribution function between regions. One part of the ship that is often damaged is the hull of the ship. The cause of hull damage is corrosion. The aspect of high and low level of corrosion on the hull is the salinity content in seawater. This study aims to determine the effect of salinity in seawater on the rate of corrosion on the hull plate with seawater media taken from the waters of the port of Tanjung Emas Semarang. This study used an experimental test method of weight loss (weight loss) referring to the ASTM G31-72 standard. With specimens made coupons to calculate the weight before immersion and weight calculation after soaking. Soaking is carried out for 7 days in the prepared corrosion installation. The results of this study indicate that seawater which has a higher salinity content than brackish water and fresh water has a higher corrosion rate than other coupon specimens.